2018
DOI: 10.1002/2211-5463.12492
|View full text |Cite
|
Sign up to set email alerts
|

Death receptor 6 promotes ovarian cancer cell migration through KIF11

Abstract: The expression of death receptor 6 ( DR 6) is abnormal in some cancer types, but the function and underlying molecular mechanisms of DR 6 in tumor progression are not yet clear. In the present study, our analysis of ovarian cancer RNA sequencing data from The Cancer Genome Atlas revealed that DR 6 is upregulated in human ovarian cancer. We confirmed that the expression level of DR 6 is upregulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Most importantly, over expression of IFIT1 or IFIT3 increased EGFR and AKT expression, which is closely related to the activation of the PI3K pathway (75). TOP2A can also activate the PI3K/AKT signaling pathway leading to cell migration (76), whereas an increased expression of KIF11 inhibited the activation of PI3K/AKT signaling pathway (77). In summary, the potential biomarker genes proposed for SLE diagnosis are closely related to PI3K pathway, and the use of PI3K inhibitors reversed the changes associated with ISG15, OAS1, OASL, and IFIT1 (72,78,79).…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, over expression of IFIT1 or IFIT3 increased EGFR and AKT expression, which is closely related to the activation of the PI3K pathway (75). TOP2A can also activate the PI3K/AKT signaling pathway leading to cell migration (76), whereas an increased expression of KIF11 inhibited the activation of PI3K/AKT signaling pathway (77). In summary, the potential biomarker genes proposed for SLE diagnosis are closely related to PI3K pathway, and the use of PI3K inhibitors reversed the changes associated with ISG15, OAS1, OASL, and IFIT1 (72,78,79).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, KIF11 is also associated with cell mobility. Relative to mass spectrometric analysis, Shi et al have found that KIF11 was co-purified with death receptor 6 (DR6), which could promote cellular migration capacity mediated by MAPK/ERK and PI3K/AKT signaling pathways for ovarian carcinoma (33). Meanwhile, KIF11 could reduce the inhibitory effects of DR6 knockdown on ovarian carcinoma cell migration, implying KIF11, to some extent, contributed to the cell mobility.…”
Section: Discussionmentioning
confidence: 99%
“…KIF11, a member of the kinesin-like protein family, was once identified as a hub gene in OC by Zhanzhan Xu et al [8], and they also found that KIF11 was potentially targeted by hsa-miR-424 and hsa-miR-381. A recent study explored whether death receptor 6 can promote OC cell migration by interacting with KIF11 and TNF receptor-associated factor 4 [40]. In this study, KIF11 was also considered a chemotherapy target for OC using cBioPortal (Fig.…”
Section: Discussionmentioning
confidence: 99%